Promotional activities for the purpose of improving the offer of travel agencies in Primorje-Gorski Kotar County-Croatia - Jasna Lasinger Siladjev (UTMS Journal of Economics, 2017)
The purpose of this paper is to stress the importance of promotional activities in advancing offers of travel agencies and their overall business profitability. More specifically, the paper examines elements of the promotional mix used by travel agencies when communicating with their customers; it is divided into six parts which delineate the characteristics of travel agencies on the tourism market, the specifics of marketing communication on the tourism market, promotional activities of travel agencies, and promotional activities of travel agencies in Primorje-Gorski Kotar County, based on previously conducted empirical research. On the turbulent tourism market, it is common that tourist demand changes from day to day; therefore, it is important to monitor these changes to create products according to new tourist needs. After creating a product, it is crucial to select that element of the promotional mix that will present the new product on the tourism market in the best possible way so that it attracts the highly coveted-tourists. To research this issue, surveys of employees in marketing departments of travel agencies were conducted which, along with other research methods, produced the final and significant results.
Keywords: M31; 330; promotion; communication; demand; product; marketplace